2015
DOI: 10.18632/oncotarget.4736
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of the novel multi-kinase inhibitor EC-70124 in triple negative breast cancer

Abstract: Disseminated triple negative breast cancer (TNBC) is an incurable disease with limited therapeutic options beyond chemotherapy. Therefore, identification of druggable vulnerabilities is an important aim. Protein kinases play a central role in cancer and particularly in TNBC. They are involved in many oncogenic functions including migration, proliferation, genetic stability or maintenance of stem-cell like properties. In this article we describe a novel multi-kinase inhibitor with antitumor activity in this can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 37 publications
(54 reference statements)
2
27
0
Order By: Relevance
“…Assays interrogating in vitro a large spectrum of kinases in the human kinome revealed that EC-70124 was highly active against IKK and JAK kinases (37,38). EC-70124 was also reported to inhibit NF-kB and JAK/STAT signaling, respectively, in glioblastoma cells (43) and in triple-negative breast cancer cells (38).…”
Section: Ec-70124 Inhibits Nf-kb and Stat3 In Prostate Cancer Cellsmentioning
confidence: 99%
See 3 more Smart Citations
“…Assays interrogating in vitro a large spectrum of kinases in the human kinome revealed that EC-70124 was highly active against IKK and JAK kinases (37,38). EC-70124 was also reported to inhibit NF-kB and JAK/STAT signaling, respectively, in glioblastoma cells (43) and in triple-negative breast cancer cells (38).…”
Section: Ec-70124 Inhibits Nf-kb and Stat3 In Prostate Cancer Cellsmentioning
confidence: 99%
“…EC-70124 was also reported to inhibit NF-kB and JAK/STAT signaling, respectively, in glioblastoma cells (43) and in triple-negative breast cancer cells (38). However, the effects of EC-70124 on STAT3 and NFkB signaling and the consequences of concomitantly targeting these key transcription factors in cancer cells with constitutive activation of both pathways have not been investigated.…”
Section: Ec-70124 Inhibits Nf-kb and Stat3 In Prostate Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytotoxic effect of IMiDs on BM-MSCs was assessed using MTT assays as previously described. 21,22 Briefly, 2 × 10 4 cells were cultured with increasing drug concentrations in 96-well plates for 48 h. To determine the chemoprotective effect of BM-MSCs a total of 2 × 10 4 BM-MSCs were plated in 96-well plates 18 h before addition of AML cells (2 × 10 4 for cell lines and 2 × 10 5 for primary cells). BM-MSC:AML co-cultures were treated with IC 25 concentrations of the AraC (77nM) and Idarubicin (7nM) and 10 µM of lenalidomide/pomalidomide for 48–72 h. Apoptosis of CD33 + AML cells was measured using the annexin-V/7-AAD apoptosis detection kit (BD Biosciences) on a FACSCanto-II cytometer using FACSDiva software (BD Biosciences) as previously described.…”
Section: Methodsmentioning
confidence: 99%